Les estructures amb «ésser» + participi passat: problemes d’ambigüitat formal - Ramos, Joan-Rafael (Caplletra. Revista Internacional de Filologia, 2004)
This article analyzes the structures of «ésser» + participle in old Catalan. It highlights the diversity of constructions that may constitute this hind of construction (compound tenses, copulatives and passives). It analyzes the methodological problems derived from structural ambiguity, and points explains the evolutionary ways that language has established to solve the problems generated by formal syncretism.